Exercising for mass casualty preparedness. (February 2022) - Moss, Rob; Gaarder, Christine
Summary: Exercising for mass casualty incidents is mandated by governing organisations with the aim of maintaining readiness within the healthcare sector for the many challenges these incidents bring. This readiness is delivered through a combination of discussion-based and operation-based exercises that are targeted to the needs of both the individuals delivering care and the needs of the overall system of patient flow and treatment. Although exercising for disaster preparedness is resource intensive, it is the repetitive, iterative nature that allows for wide staff capture and exposure along with continual improvement of plans. Having been recently involved in exercising is also likely to increase the confidence of staff and makes them feel better prepared. Exercising should be tailored to the needs and likely challenges of each healthcare system. A cycle of design, challenge, and redesign should target areas of greatest need and greatest benefit. The conventional advice, when introducing exercising, is to start small and build up over time with repeated exercises that demonstrate increasing response capability. However, some organisations would benefit from an exercise that lays bare shortcomings and acts to galvanise change.